IMPLICATIONS OF OPEN EDUCATIONAL RESOURCES FOR YOUR MEMORY OF LINKS - Sarsa, Javier (European Scientific Journal, ESJ, 2014)
Open contents also open the door for acquiring a large variety and quantity of new knowledge. They are always available for us, and once they are located and selected, we only need to wait as long as necessary to have enough time to learn them. Storing contents on very different ICT devices may contribute to freeze the overload of our memory, but some studies affirm that a smaller cognitive effort is made when we know the contents are ready out there, in the Web. This article is focused into the implications of incorporating different digital open resources in your ‗Memory of Links‘ (MoL). This concept, the MoL, represents the space of memory which needs to be allocated in the brain for storing those links. The seeking and selection processes, the memorization and storage of links, the ability to remember some notions about the stored information and the need of organization of those linked resources in external devices vary according to the different individuals. This fact has been checked through a study carried out with 58 students who were surveyed and interviewed in order to obtain information about the way they filled their MoL. The individuals showed distinct behaviors in respect of the number and type of the stored links, storage devices, structuration of information, link management tools, etc.